Beyond the third moment? Mapping the state of qualitative tourism research. Issue 7 (2nd April 2020) - Wilson, Erica; Mura, Paolo; Sharif, Saeed Pahlevan; Wijesinghe, Sarah N. R.
ABSTRACT: This paper poses a central question: what is the present moment in qualitative tourism research? To answer this, the authors review the state of contemporary qualitative tourism research over the past decade (2007–2017), against current progress in the social sciences. Specifically, a systematic bibliometric analysis of tourism journals was undertaken to determine how tourism scholarship maps against Denzin and Lincoln's social science 'moments'. These moments prove useful in heuristically framing the development of qualitative social research and thinking; from early moments characterized by positivist ways of knowing, through to later moments where scholars struggle through and beyond the crisis of representation. Using an adapted moments-based framework, our analysis of 1541 qualitative papers across 51 tourism journals indicates that the majority of papers are emblematic of 'early moment' thinking. Despite clear evidence of a crisis of representation in some areas, and an increase in the number of qualitative papers published, there is a lack of 'later moment' thinking, methodology and/or approach. The political, social and philosophical constraints and opportunities presented by these findings are discussed.